Tourism and covid-19 in three European cities. Change in persistence - Gloria Claudio-Quiroga; Cecilia Font de Villanueva; Luis Alberiko Gil-Alana (Cogent Social Sciences)
This article deals with the analysis of persistence in tourism in three European cities, namely, London, Manchester and Berlin. We consider hotel occupancy rate data with data beginning at October 1997 (in London), at March 2004 (in Berlin), while those in Manchester start at January 2006. All data ends at February 2024. Fractional integration methods are used, and the results indicate changes in the persistence pattern of the series due to the Covid-19 pandemic. Thus, before the pandemic, the results indicate that the integration order was less than 1 in the three series, implying transitory shocks. However, with the inclusion of data from 2020 to February 2024, the order of integration substantially increases in all cases, and the unit root hypothesis cannot be rejected, implying the permanent effects of shocks. Our results show that the effect of Covid-19 has been especially significant in hotel occupancy rate data in the three cities analyzed, indicating that strong policy measures are needed to reassume pre-crisis trends in the tourism industry.